128 Bright blood t2 weighted MRI has higher diagnostic precision and accuracy than dark blood stir MRI for assessment of the ischaemic area-at-risk and myocardial salvage in acute myocardial infarction. (9th June 2011) - Payne, A R; Casey, M; McClure, J; McGeoch, R; Murphy, A; Woodward, R; Saul, A; Gilchrist, J; Clark, C; Oldroyd, K G; Tzemos, N; Berry, C
Abstract : Background: T2-weighted MRI reveals myocardial oedema and enables estimation of the ischaemic area-at-risk and myocardial salvage in patients with acute myocardial infarction (MI). We compared the diagnostic accuracy of a new bright blood T2-weighted with a standard black blood T2-weighted MRI in patients with acute MI. Methods: A breath hold bright blood T2-weighted ACUTE pulse sequence with normalisation for coil sensitivity and a breath hold T2 dark blood short τ inversion recovery (STIR) sequence were used to depict the area-at-risk in 54 consecutive acute MI patients. Infarct size was measured on gadolinium late contrast enhancement images. Results: Compared with dark blood T2-weighted MRI, consensus agreements between independent observers for identification of myocardial oedema were higher with bright blood T2 -weighted MRI when evaluated per patient (p<0.001) and per segment of left ventricle (p<0.001). Compared to bright blood T2-weighted MRI, dark blood T2-weighted MRI under-estimated the area-at-risk compared to infarct size (p<0.001). The 95% limits of agreement for inter-observer agreements for the ischaemic area-at-risk and myocardial salvage were wider with dark blood T2-weighted MRI than with bright blood T2-weighted MRI. Bright blood enabled more accurate identification of the culprit coronary artery with correct identification in 94% of cases compared to 61% for dark blood (p<0.001). Conclusion: Bright blood T2-weighted MRI has higher diagnostic accuracy than dark blood T2-weighted MRI. Additionally, dark blood T2-weighted MRI may underestimate area-at-risk and myocardial salvage.